DEVELOPMENT OF ETHNOSCIENCE-BASED INTEGRATED SCIENCE E-MODULES USING FLIPBOOKS ON THE THEME OF REBON SHRIMP PASTE - Kamila, Kamila; Ahied, Mochammad; Hadi, Wiwin Puspita; Putera, Dwi Bagus Rendy Astid; Sutarja, Maria Chandra (Jurnal penelitian pendidikan IPA, 2024)
Integrated science learning in ethnoscience is very important because students can know the concrete form of local culture by constructing indigenous knowledge of the community in the process of making shrimp paste into scientific knowledge which is implemented through learning media in the form of e-modules. The purpose of this study was to produce an e-module and determine the level of validity, and student readability to an integrated science-based e-module based on ethnoscience using a flipbook with the theme of rebon shrimp paste. This type of research is development research using the ADDIE development model. The population in this study were all students of class VIII MTsN 2 Sumenep with a sample of class VIII-B. Sampling using purposive sampling technique. The instruments used were validation sheets of media experts, material experts, science teachers, and questionnaires student readability. The results showed that: 1) The results of the media aspect validity were 88.74% and the reliability value was 95.71% with very valid and very reliable categories. The value of the validity of the material aspect is 86.11% and the reliability value is 89.66% with a very valid and very reliable category. 2) Students' readability scores a percentage value of 88.18% with a very good category.